PENERIMAAN DARI PEMERINTAH PUSAT, UKURAN LEGISLATIF, DAN TEMUAN AUDIT TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI KASUS PADA PEMERINTAH DAERAH KABUPATEN/KOTA DI ACEH) - Fuadi, M. Zahrul; Asmara, Jhon Andra (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study aims to see the influence of regional distribution characteristics, legislative measures, and audit findingsagainst the level of disclosure of Preliminary Unaudited Regional Government Financial Report. The population that used in this study is the District and Urban District Government in Aceh Province during 2015-2017. This study usespurposive sampling techniques, so the selection of samples is done by according to specific considerations or goals.The independent variables examined in this study are regional government size, regional independence, intergovernmental revenue, legislative measures, and audit findings. The dependent variable is the level of disclosure of Preliminary Unaudited Regional Government Financial Report. The type of data used in this study is secondary data. The analysis used in this study is multiple linear regression. The data is processed by using the SPSS software test tool. The results showed that variables of regional government size, regional independence, intergovernmental revenue, legislative measures, and audit findings have positive affect on the level of disclosure of Preliminary Unaudited Regional Government Financial Report. Partially, intergovernmental revenue and audit findings have negative affect on the level of disclosure of Preliminary Unaudited Regional Government Financial Report, while regional government measures, regional independence and legislative measures have no significant effect on the level of disclosure of Preliminary Unaudited Regional Government Financial Report.